Fluorescence Endomicroscopy Imaging of Mesenchymal Stem Cells in the Rat Lung. (4th May 2018) - Perez, Jessica R.; Ybarra, Norma; Chagnon, Frederic; Lesur, Olivier; Seuntjens, Jan; Naqa, Issam El
Abstract: Stem cell therapy has shown great promise for organ repair and regeneration. In the context of lung disease, such as radiation‐induced lung damage (RILD) in cancer radiotherapy, mesenchymal stem cells (MSCs) have shown the ability to reduce damage possibly due to their immunomodulatory properties and other unknown mechanisms. However, once MSCs are transplanted into the body, little is known as to their localization or their mechanisms of action. In this work, we proposed, implemented, and validated a fluorescence endomicroscopy (FE) imaging technique that allows for the real‐time detection and quantification of transplanted pre‐labeled MSCs in vivo and tracking in a rat model. This protocol covers aspects related to MSCs extraction, labeling, FE imaging, and image analysis developed in a RILD rat model but applicable to other biological systems. © 2018 by John Wiley & Sons, Inc.